A competency framework and measure for psychologists: the psychometric assessment of the Competencies of Professional Psychology Rating (COPPR) Scales - Kylie Rice; Stephanie E. Banner; Nicola Schutte; Adam J. Rock (Australian Journal of Psychology)
Objective The Competencies of Professional Psychology Rating (COPPR) Scales provide a standardised, multi-dimensional framework for conceptualising and measuring the competencies of registered psychologists across all domains of practice. The COPPR Scales consist of both a self-report version for practitioner self-evaluation (the COPPR-S) and an observer version (COPPR-O) for supervisors and educators to rate competence of trainees. These scales have utility for psychologists to self-assess their competence within self-reflection, for supervisors to rate trainee competence, and for research and educational contexts.Method Following on from an initial pilot study, this study provides a psychometric evaluation of the COPPR-S, including tests of dimensionality, reliability and validity, with a sample of Australian Psychologists (N = 211).Results The confirmatory factor analysis provided support for the structure of the measure and all 11 domains of competence. Internal consistency was calculated for each of the domains and the total score, and strong support for convergent and divergent validity was obtained. In addition, the COPPR-S was able to discriminate between the three participant registration groups of provisional registration, general registration, and additional endorsements. Thus, strong support for the COPPR-S as a conceptual model of psychologist competencies and multi-dimensional measure was provided, and the items are presented for use in practice, education and research.